2021
DOI: 10.1111/gcbb.12804
|View full text |Cite
|
Sign up to set email alerts
|

Brassica carinata: Biology and agronomy as a biofuel crop

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 139 publications
3
27
0
Order By: Relevance
“…Carinata has demonstrated greater yield potential compared to camelina ( Camelina sativa L. Crantz), rapeseed ( Brassica napus L.), and pennycress ( Thlaspi arvense L.) grown in a similar rotation (Gesch et al, 2015), and may be well suited as a winter crop in the southeastern (SE) US (Seepaul, Bliss, et al, 2016; Seepaul et al, 2018). These features may allow the incorporation of carinata into existing cotton ( Gossypium hirsutum L.)–peanut ( Arachis hypogaea L.) cropping systems in the SE as a winter crop with modest modification to existing infrastructure (Boote et al, 2021; Seepaul, Bliss, et al, 2016; Seepaul et al, 2021; Tiwari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Carinata has demonstrated greater yield potential compared to camelina ( Camelina sativa L. Crantz), rapeseed ( Brassica napus L.), and pennycress ( Thlaspi arvense L.) grown in a similar rotation (Gesch et al, 2015), and may be well suited as a winter crop in the southeastern (SE) US (Seepaul, Bliss, et al, 2016; Seepaul et al, 2018). These features may allow the incorporation of carinata into existing cotton ( Gossypium hirsutum L.)–peanut ( Arachis hypogaea L.) cropping systems in the SE as a winter crop with modest modification to existing infrastructure (Boote et al, 2021; Seepaul, Bliss, et al, 2016; Seepaul et al, 2021; Tiwari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…napus (napus) and B . rapa with high oleic acid, low erucic acid, and low glucosinolate content are grown widely as major edible oilseed crops in Europe, North America, South America, Australia, and China (Seepaul et al, 2021). Brassica juncea with high erucic acid and glucosinolate content is mostly grown in the South Asian subcontinent to meet the edible oilseed demand (Becker et al, 1995; Gómez‐Campo, 1999; Kjellström, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Seepaul, Kumar, Iboyi, et al (2021) provide details of the origin, distribution, genomic resources, morphology, phenology, reproduction, and agronomy of carinata based on studies across the world. It was found that carinata is adaptable to diverse growing regions, cropping systems, and management regimes with demonstrated potential to be grown on the continents of Asia, Africa, North America, South America, Europe, and Australia either as a spring or winter crop in double‐cropped systems.…”
Section: Development Of Carinatamentioning
confidence: 99%